The Effect of Providing Additional Employee Income on Employee Performance - Haedar Akib; Khusnul Hatimah; Herlina Sakawati (Pinisi Journal of Education and Management, 2023)
Additional employee income is compensation received by civil servants which aims to improve employee performance. This study aims to determine the effect of providing additional employee income on employee performance at the Office of the Bureau of Personnel and Human Resources Development in Barru Regency. This research is a correlation research using a quantitative approach. Data collection techniques using the observation method, questionnaire/questionnaire method and documentation method. Data analysis techniques in this study used descriptive analysis techniques and inferential statistical analysis. The results showed that the indicators of the additional employee income variable were in the very good category, while the employee performance variables were in the very high category. So it can be concluded that there is a significant influence between the provision of additional employee income on employee performance at the Office of the Bureau of Personnel and Human Resources Development in Barru Regency. Providing additional employee income will improve performance and make employees aware of the duties and responsibilities given. The results of this study stated that after getting additional employee income, employees were more active and diligent at work so that their performance increased.Achmad Ruki. (2011). Sistem Manajemen Kinerja. In Open Journal of Internal Medicine. https://doi.org/10.4236/ojim.2011.13011Aisha, N., & Kurnia, E. (2018). Pengaruh Kuantitas dan Kualitas terhadap Citra Merek pada Universitas Muhammadiyah Sumatera Utara. Jurnal Samudra Ekonomi Dan Bisnis, 9(2).Amirullah, A. H., & Darwis, M. (2015). Upaya Peningkatan Kinerja Pegawai pada Biro Administrasi Akademik dan Kemahasiswaan Universitas Negeri Makassar. Jurnal Office, 1(2), 180–184.Asriel, A. S., Armiati, & Frista, L. (2016). Manajemen Kantor. Kencana.Awaliah, N., Amirullah, A. H., & Saleh, S. (2015). Kinerja Pegawai Negeri Sipil pada Kantor Kementerian Agama Kota Makassar. Jurnal Office, 1(1), 13–17.Azis, M. D. (2018). Pengaruh Motivasi Kerja , Kompetensi , Dan Kompensasi Terhadap Kinerja Pegawai Pada Kantor Pelayanan Pajak Pratama Makassar Selatan. 2(2), 1–11.Barru Regent Regulation Number 22 of 2018 Concerning Additional Income for Civil Servants, Peraturan Bupati Barru Nomor 22 Tahun 2018 Tentang Tambahan Penghasilan Pegawai Negeri Sipil (2018).Erawati, I., Darwis, M., & Nasrullah, M. (2017a). Efektivitas Kinerja Pegawai pada Kantor Kecamatan Pallangga Kabupaten Gowa. Jurnal Office, 3(1), 13–18.Erawati, I., Darwis, M., & Nasrullah, M. (2017b). Efektivitas Kinerja Pegawai pada Kantor Kecamatan Pallangga Kabupaten Gowa. Jurnal Office, 3(1), 13–18.Handayani, S. (2017). Pengaruh Kompensasi Finansial Terhadap Kinerja Pegawai Harian Lepas di Dinas Lingkungan Hidup dan Kebersihan Kota Palembang. Jurnal Ilmiah Ekonomi Global Masa Kini, 8(1), 12–20.Hatta, H. (2020). Pengaruh Kompensasi terhadap Kinerja Pegawai pada Balai Rehabilitasi Sosial Penyandang Disabilitas Fisik Wirajaya Makassar. Universitas Negeri Makassar.Isma, E. W., Darwis, M., Saleh, S., & Salam, R. (2017). Kualitas Pelayanan Administrasi pada Puskesmas Gattareng Kecamatan Gantarang Kabupaten Bulukumba. JURNAL ILMU ADMINISTRASI PERKANTORAN (JIAP), 21–28.Kurniawan, M. R., & Pujiyono. (2918). Modus Operandi Korupsi Pengadaan Barang dan Jasa Pemerintah oleh PNS. Law Reform, 14(1).Massuanna, M., & Niswaty, R. (2013). Efektivitas Pelaksanaan Tugas Sekretaris pada Kantor Komisi Pemilihan Umum Provinsi Sulawesi Selatan.Muizu, W. O. Z., Evita, S. N., & Suherman, D. (2016). Disiplin kerja dan pengaruhnya terhadap kinerja pegawai negeri sipil. PEKBIS (Jurnal Pendidikan Ekonomi Dan Bisnis), 8(3), 172–182.Norani, M., Amirullah, A. H., & Darwis, M. (2015). Efektivitas Kinerja Pegawai pada Kantor Kementerian Agama Kota Makassar. Jurnal Office, 1(1), 1–7.Ridwan, R. M., Darwis, M., & Niswaty, R. (2018). Pengaruh Tata Ruang Kantor terhadap Kinerja Pegawai Negeri Sipil pada Kantor Badan Pusat Statistik Provinsi Sulawesi Selatan. UNIVERSITAS NEGERI MAKASSAR.Salam, R., Akhyar, M., Tayeb, A. M., & Niswaty, R. (2017). Peningkatan Kualitas Publikasi Ilmiah Mahasiswa dalam Menunjang Daya Saing Perguruan Tinggi. Jurnal Office, 3(1), 61–65.Saleh, S., Akib, H., & Guntur, M. (2019). Disiplin kerja pegawai dalam peningkatan pelayanan perizinan pada kantor dinas penanaman modal dan pelayanan terpadu satu pintu (ptsp) kabupaten gowa. Universitas negeri makassar.Saleh, S., & Darwis, M. (2016). Pengaruh Tunjangan Kinerja Terhadap Kinerja Pegawai Pada Bauk Universitas Negeri Makassar. Jurnal Ilmiah Ilmu Administrasi Publik, 5(2), 121–130.Sugiyono. (2018). Metode Penelitian Pendidikan Kuantitatif, kualitatif dan R&D. Alfabeta.Sugiyono. (2019). Meotode penelitian kuantitatif,kualitatif, da R&DP. Alfabeta, bandung.Wairooy, A. (2017). Pengaruh Disiplin Kerja dan Kompensasi Terhadap Kinerja Karyawan pada PT. Pertamina (Persero), Tbk. Pemasaran Region VII Makassar. Jurnal Ad’ministrare: Jurnal Pemikiran Ilmiah Dan Pendidikan Administrasi Perkantoran, 4(1), 15–24.Wibowo. (2011). Manajemen Kinerja. Rajawali Pers.Yusuf, N. (2018). Pengaruh Kepemimpinan, Tanggung Jawab, Kedisiplinan Dan Kerjasama Terhadap Kinerja Pegawai di Universitas Gorontalo. 25.